Investigating ecological drivers and impacts of vegetation change in sub Antarctic tundra - Van Der Merwe, Stephni (Department of Biological Sciences, 2025)
Understanding the impact of environmental change on vegetation dynamics requires considering the individualistic responses of plant species, which are influenced by their specific habitat requirements and biotic interactions. For instance, habitat generalist species often have broad environmental tolerance, and may be able to adapt to and often dominate in dynamic or disturbed environments, compared to specialists that are adapted to specific environmental conditions and thus have more restricted tolerance to change. This study explores the potential for the combination of topographic, climatic, edaphic and biotic factors to influence different vascular plant species distributional and cover changes in response to the key drivers of change in the sub-Antarctic, focusing on Marion Island (MI). Given the recent origin and relative species poverty of the sub-Antarctic flora, changes in vegetation are expected to result from individual responses rather than collective trends across the entire flora or its communities. To evaluate the appropriate scale for vegetation assessment in species-poor environments, the classification of vegetation on MI was revisited. Various modern classification techniques were used to classify vascular plant species data, and the resulting classifications were compared with previous units. Due to the limited development of strong plant assemblages with discrete boundaries in the sub-Antarctic islands, community-level classification may not be suitable in such species-poor environments. Consequently, this study proposes a species-level approach aligned with continuum theory rather than community theory for more accurate vegetation monitoring in species-poor environments. Since the 1950s, MI has experienced changes in temperature, precipitation, wind conditions, and biotic interactions, with plant species thus experiencing altered environmental conditions. To investigate the vegetation cover changes across different habitats, repeat photography between 1965 and 2020 was used. Results showed an overall increase in vegetation cover in most habitats over the past five decades, accompanied by rapid drying, rising mean air temperature, changing wind direction, increased invasive plant species cover, and higher invasive house mouse abundance. Climate change and invasive species were identified as the primary interactive drivers of vegetation change. The increase in cover was primarily driven by more responsive species, such as habitat generalists, while habitat specialists either showed minimal changes or a decrease in cover. Since edaphic properties are an often overlooked component of habitat suitability or changes therein, the edaphic properties were modelled for the first time on MI to determine the spatial variation of key soil 4 properties across MI using boosted regression trees. The impact of temperature change on plant species distribution was then examined through species distribution models incorporating edaphic properties along with climatic, topographic and biotic factors. By considering a combination of climatic (changing), biotic, and non-climatic (fixed) predictors, the study aimed to determine the direction and constraints of species distributional changes under past and future temperature scenarios. Although the habitat requirements of vascular plant species on MI were species-specific, with species distributions predicted by differential variables, the responses of most generalist plant species to warming were similar, whereas responses of specialist species were similar. With continued warming, the habitat suitability of generalist plant species were predicted to increase on MI, within the physical constraints imposed by the environment, and toward the west, whereas the habitat suitability of most specialist species was not predicted to increase with warming. The results support the overarching hypothesis of this study that vegetation change on MI occurred as a consequence of the interaction of factors, key among them being climate change and invasive species. This research emphasises the individualistic responses of vascular plant species to environmental change in species-poor and/or young environments. Most habitat generalists have increased in cover and expanded their ranges, and these trends are projected to continue with warming, within the physical limitations of the environment. In contrast, the habitat suitability of specialist species show limited change, with no significant changes in cover observed or changes in range predicted with warming. Consequently, a comprehensive assessment of habitat suitability for different plant species requires considering a combination of topographic, climatic, edaphic, and biotic factors. This study highlights the importance of studying individualistic responses and understanding the specific habitat requirements of individual vascular plant species, which may be overlooked when focusing solely on species assemblages